2022
DOI: 10.3390/polym14061251
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Property Characterization of Long-Glass-Fiber-Reinforced Polypropylene Composites Processed Using a Three-Barrel Injection Molding Machine

Abstract: Processing equipment and parameters will highly influence the properties of long-fiber-reinforced injection-molded thermoplastic composites, leading to different fiber lengths and orientations. Thus, maintaining fiber length during the injection molding process is always a big challenge for engineers. This study uses long-glass-fiber-reinforced polypropylene with 25 mm fiber length and a special-built novel injection molding machine with a three-barrel injection unit, including a plasticizing screw, an injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Figure 2 shows the 3D CAD model and dimensions of a power case. Both the cover and chassis of a 3C power case were fabricated by plastic injection molding via polycarbonate (PC) [24] using a plastic injection molding machine (KT2S, Kinki Inc., Taipei city, Taiwan) [25]. The process parameters involve injection pressure of 18 MPa, injection speed of 80 mm/s, and cooling time of 10 s. The length, width, and height of the cover are 42.8 mm, 26 mm, and 51.8 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the 3D CAD model and dimensions of a power case. Both the cover and chassis of a 3C power case were fabricated by plastic injection molding via polycarbonate (PC) [24] using a plastic injection molding machine (KT2S, Kinki Inc., Taipei city, Taiwan) [25]. The process parameters involve injection pressure of 18 MPa, injection speed of 80 mm/s, and cooling time of 10 s. The length, width, and height of the cover are 42.8 mm, 26 mm, and 51.8 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Under the influence of Finite Element Analysis results, the steel car door has been modified with glass fiber composite materials. Liou et al [12] have made an experimental investigation to perform process characterization for the specimen laminates. It is observed that the process parameters have played no role to affect the fiber angles because of the lengthy fibers.…”
Section: Introductionmentioning
confidence: 99%
“…This influence is more important in the micro-injection molding process, in which the melt flow length must be increased in the product’s micro-features. Because micro-injection molds are low cost and have the potential for high-volume production, they are used to manufacture a variety of polymer components in the injection molding field [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, the most common applications of micro-injection molding are in micro-devices [ 9 , 10 ], optical structures [ 11 , 12 , 13 , 14 ], and micro-fluidic devices [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%